Nature observations between tourism, scientific data and pure appreciation - Procheş, Şerban (Frontiers in Ecology and Evolution, 2024)
Nature observations are at the core of both nature-based tourism and citizen science. The movement limitations associated with the Covid-19 pandemic have created a window during which tourism nose-dived, but online citizen science platforms flourished primarily through the posting of ‘backyard’ observations. Beyond citizen science, a return to nature during this period appears to have been important in supporting mental health, especially in city dwellers, and this has resulted in a renewed interest in studying nature appreciation. Here I attempt to bring together these different facets of nature watching research, defined by divergent philosophical underpinning and following different methodologies. I use the findings of tourism and citizen science studies to summarize observer motivations, and place these in a nature appreciation framework. I argue that this framework can be used towards maintaining a balance between diverse goals: reducing observer biases in citizen science, enhancing observer experience in nature-based tourism, and maximizing the therapeutic effects of being exposed to nature.